COVID-19 vaccine or booster uptake and hesitancy for children aged 6 months–5 years in the United States: A national descriptive study using the household pulse survey between March and May 2023 - Park, Chulwoo; Zabala, Pyramida Vagoyan (Elsevier, 2024)
The Centers for Disease Control and Prevention recommends that children aged 6 months–5 years (children under 5) receive multiple doses of COVID-19 vaccine, including updated (bivalent) COVID-19 vaccine. However, since the updated vaccines became available for children under 5, there has been limited knowledge regarding hesitancy toward the original vaccine or boosters in vaccinating children. To address this gap, this study utilized data from the Household Pulse Survey conducted from March 1, 2023 to May 8, 2023 (Phase 3.8). The purpose of the study was to examine the proportion of children under 5 who had received at least one dose of COVID-19 vaccine and to assess the likelihood of vaccination, categorized as willingness to vaccinate, moderate hesitancy, and strong hesitancy. Additionally, we identified sociodemographic factors that may influence the level of vaccine hesitancy for children. Overall, 24.5 % (95 % CI: 22.2–26.8) of children under 5 had received at least one dose of the COVID-19 vaccine, with the highest percentage among non-Hispanic Asians (42.1 %, 95 % CI: 36.4–47.8). Respondents who had not received the vaccine showed a statistically significant decrease in their inclination to vaccinate children. There was a higher level of vaccine hesitancy among females compared to males regarding vaccinating children under 5. As household income and educational attainment decreased, there was an observed increase in the proportion of individuals showing strong vaccine hesitancy. Households without health insurance had significantly lower vaccine uptake and higher rates of strong vaccine hesitancy compared to those with health insurance. Parents, guardians, and healthcare providers play essential roles in vaccinating children under 5. Targeted interventions are needed to address vaccine hesitancy and promote the importance of booster doses in the vaccination of children.
Keywords: Test for proportions; COVID-19 vaccine; Updated COVID-19 booster; Descriptive study; Vaccine hesitancy; Children aged 6 months–5 years (children under 5)